2009
DOI: 10.1038/sj.bjc.6605097
|View full text |Cite
|
Sign up to set email alerts
|

Association of apolipoprotein E polymorphisms and dietary factors in colorectal cancer

Abstract: ApoE single nucleotide polymorphisms (SNPs) Cys112Arg (Epsilon-4), and Arg158Cys (Epsilon-2) have been implicated in cardiovascular and Alzheimer's disease, but their role in colorectal cancer (CRC) has not been extensively studied. We investigated whether ApoE polymorphisms alone or in combination with dietary factors selectively contribute to mismatch-repair (MMR) proficient (microsatellite stable/low or MSS/L) vs deficient (microsatellite unstable or MSI-H) CRCs. We carried out a case -control study with 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…At the organismal level, deregulation of mTOR complex activity has been linked to aging and to diseases like diabetes or cancer (11,(23)(24)(25)(26). Furthermore, mTOR inhibitors have been used to extend lifespan in mice and in clinical treatments of several human cancers, including mantle cell lymphoma, endometrial cancer, and renal cell carcinoma (26,73,74).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the organismal level, deregulation of mTOR complex activity has been linked to aging and to diseases like diabetes or cancer (11,(23)(24)(25)(26). Furthermore, mTOR inhibitors have been used to extend lifespan in mice and in clinical treatments of several human cancers, including mantle cell lymphoma, endometrial cancer, and renal cell carcinoma (26,73,74).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies point to the importance of nutrients in the etiology of some major diseases, such as insulin-resistant obesity (23) or cancer (24,25) and in the aging process (11,26). In humans, circulating amino acid levels are elevated in obese individuals, and this is related to an increase in insulin resistance (23,27,28).…”
mentioning
confidence: 99%
“…The effect of apoE genotypes has been investigated in relation to breast, colorectal, biliary tract, prostate cancer and hematologic malignancies (7,(16)(17)(18)35), with conflicting results. Trompet et al (19) recently addressed the relationship between cholesterol and cancer by studying both the effect of plasma cholesterol levels and apoE isoforms on overall cancer risk during a 3-year follow-up study in a large elderly cohort (19).…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been called "Mendelian randomization" (14,15), and it has been recently adopted to evaluate the association between cholesterol levels and cancer risk by using the apoE genotype as a surrogate for cholesterol levels. Results, however, are largely conflicting (7,(16)(17)(18). Trompet et al (19) recently reported the results of a large cohort study measuring the apoE genotype, plasma cholesterol levels, and overall cancer incidence and mortality during a 3-year follow-up period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation